Influence of film structure on mobilities of charge carriers in conducting polymers - Harima, Yutaka; Jiang, Xiaoqing; Patil, Rahul; Komaguchi, Kenji; Mizota, Haruo (Electrochimica Acta, 2007)
Two sorts of poly(3-hexylthiophene) (PHT) films with the same chemical compositions were prepared, and their electrochemical, spectroscopic, and transport properties were studied with a special interest in a possible influence of film structure on mobilities of charge carriers. One of the PHT films was electrochemically synthesized using 3-hexylthiophene as a monomer (as-grown film) and the other was obtained by dissolving the as-grown film in chloroform and then casting the polymer solution (cast film). A clear difference was observed in the mobility versus doping level plot between the two sorts of PHT films, demonstrating that the difference is caused only by a distinction in film structure. An initial decreasing feature of the mobility plot observed for the cast films was accounted for in terms of swelling of the films at an early stage of doping. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: Doping; electrosynthesis; mobility; poly(3-hexylthiophene); swelling

Transport study on as-grown and cast films of electrogenerated poly(3-hexylthiophene) - Jiang, Xiaoqing; Harima, Yutaka; Patil, Rahul (Materials Letter, 2007)
Two kinds of poly(3-hexylthiophene) films with identical chemical compositions are prepared. One of the films is obtained by electropolymerization of 3-hexylthiophene (as-grown film) and the other is prepared by casting a solution dissolving the as-grown film (cast film). A clear difference is found in the mobility vs. doping level plots between the as-grown and cast films and its reason is discussed. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: mobility; poly(3-hexylthiophene); swelling; thin film; transport mechanism

Synthesis of amphiphilic isoindigo co-polymers for organic field effect transistors: A comparative study - Dharmapurikar, Satej S.; Arulkashmir, Arulraj; Mahale, Rajashree Y.; Chini, Mrinmoy Kumar (Journal of the apllied polymer science, 2017)
In this work, the amphiphilic isoindigo (am-iInd) based conjugated polymers namely poly(am-iInd-DT) and poly(am-iInd-TT) and their regular counterpart poly(reg-iInd-DT) and poly(reg-iInd-TT) were synthesized to compare their opto-electronic and charge transport properties. They were used to fabricate organic field effect transistors. Charge transport properties in conjugated polymers depend upon intermolecular interaction which is strongly affected by the nature of side chains. The amphiphilic nature of the conjugated polymers has little impact on the charge transport properties. The charge carrier mobility of amphiphilic conjugated polymers was comparable with the regular polymers except poly(reg-iInd-DT) which can be correlated by X-ray diffraction and thin film morphology. (c) 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2017, 134, 45461.
Keywords: Alkyl; Applications; Conducting polymers; Copolymers; Optical and Photovoltaic applications; conjugated polymers; High-performance; mobility; Packaging; Semicondoctors; Side-chains; Solar-cells; Thin-film Transformer

Thiol and halometallate, mutually passivated quantum dot ink for photovoltaic application - Mandal, Debranjan; Goswami, Prasenjit N.; Rath, Arup K. (ACS Applied Materials & Interfaces, 2019)
Tunable-band-gap colloidal QDs are a potential building block to harvest the wide-energy solar spectrum. The solution-phase surface passivation with lead halide-based halometallate ligands has remarkably simplified the processing of quantum dots (QDs) and enabled the proficient use of materials for the development of solar cells. It is, however, shown that the hallometalate ligand passivated QD ink allows the formation of thick crystalline shell layer, which limits the carrier transport of the QD solids. Organic thiols have long been used to develop QD solar cells using the solid-state ligand exchange approach. However, their use is limited in solution-phase passivation due to poor dispersity of thiol-treated QDs in common solvents. In this report, a joint passivation strategy using thiol and halometallate ligand is developed to prepare the QD ink. The mutually passivated QDs show a 50% reduction in shell thickness, reduced trap density, and improved monodispersity in their solid films. These improvements lead to a 4 times increase in carrier mobility and doubling of the diffusion length, which enable the carrier extraction from a much thicker absorbing layer. The photovoltaic devices show a high efficiency of 10.3% and reduced hysteresis effect. The improvement in surface passivation leads to reduced oxygen doping and improved ambient stability of the solar cells.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Reduction of hydroxyl traps and improved coupling for efficient and stable quantum dot solar cells - Mandal, Debranjan; Dambhare, V. Neha; Rath, Arup K. (ACS Applied Materials & Interfaces, 2021)
Progress in quantum dot (QD)-based solar cells has been underpinned by the improvements in surface passivation and advancements in device engineering. Acute control over the surface properties is crucial to restrict the formation of in-gap trap states and improve the QD coupling in achieving conducting QD films. In this report, we demonstrate a solution-phase hybrid passivation strategy, which is beneficial in removing detrimental hydroxyl traps and improving the coupling between QDs by reducing the interdot distance. Advancement in surface passivation is translated to the long carrier lifetime, higher carrier mobility, and superior protection toward degradations in QD solids. The performance of solar cell devices is increased by 26% to reach an efficiency of 10.6%, compared to the state-of-the-art lead halide passivated solar cells. The improvement in solar cell performance is supported by the reduction of trap states and an 80 nm increase in thickness of the light-absorbing QD layer.
Keywords: ligand; mobility; quantum dot; solar cell; surface passivation

Significance of secondary forces toward improving the charge carrier mobility of Isoindigo based conjugated small molecules - Dharmapurikar, Satej S.; Kashmir, Arulraj Arul; Kumari, Tanya; Kalalawe, Virbhadra; Kanetkar, Maruti; Chini, Mrinmoy Kumar (Chemical Physics Letters, 2021)
The charge carrier mobility of conjugated small molecules (CSMs) depends on the intermolecular interactions and morphology. Herein, we report the synthesis of CSMs having different side chains. Hydrogen bonding, lipophilic imbalance and van der Waals interactions are imparted through the asymmetric substitution of Isoindigo. The secondary forces impact thin film morphology, and charge carrier mobility. The CSMs having van der Waals interaction further shows higher charge carrier mobility as a function of improved morphology, and increased temperature. The highest mobility of 0.15 cm2/Vs has been achieved for CSMs with van der Waals interaction.
Keywords: Conjugated small molecules; Isoindigo; mobility; OFET; Secondary force